2004
DOI: 10.1300/j128v02n04_01
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of SIV-Induced Ocular Pathology in Macaque Monkeys

Abstract: Simian immunodeficiency virus has been shown to cause acquired immunodeficiency syndrome in macaque monkeys. Data gathered from clinical examination and fundus photography have shown that the lentivirus is capable of the induction of choroidal lesions and retinal hemorrhages in the macaque. These findings demonstrate the potential value of the macaque monkey eye as a model of the retinal pathology routinely seen in human AIDS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…We used this model system to explore the effects of morphine on pathogenesis of the infection with focus on this CNS aspect of the infection. SIVmacR71/17E has been shown in earlier studies to cause AIDS and neurological disease assessed pathologically Johnson et al 2004), stereologically , behaviorally (Marcario et al 1999a and b), and neurophysiologically (Raymond et al , 2000 in Indian Rhesus Macaques. The present study showed that infected animals treated with morphine failed to develop ELISPOT responses, in contrast to the infected, non-treated animals that did develop the CMI response.…”
Section: Introductionmentioning
confidence: 94%
“…We used this model system to explore the effects of morphine on pathogenesis of the infection with focus on this CNS aspect of the infection. SIVmacR71/17E has been shown in earlier studies to cause AIDS and neurological disease assessed pathologically Johnson et al 2004), stereologically , behaviorally (Marcario et al 1999a and b), and neurophysiologically (Raymond et al , 2000 in Indian Rhesus Macaques. The present study showed that infected animals treated with morphine failed to develop ELISPOT responses, in contrast to the infected, non-treated animals that did develop the CMI response.…”
Section: Introductionmentioning
confidence: 94%